FLIPBOOK INTERAKTIF BERBASIS CERITA PADA PERKALIAN BILANGAN CACAH: STUDI VALIDITAS - Thahira, Adelia Nur; Sastrawati, Eka; Hidayat, Akhmad Faisal (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This development research was motivated by observations at SD Negeri 74/III Dusun Baru, which showed that mathematics instruction on whole-number multiplication had not yet made optimal use of technology-based media. As a result, students were less enthusiastic, less active, and experienced difficulties in understanding the concepts because learning was still dominated by teacher explanations without interactive media support to help visualize the concepts. The focus of the study was to develop a story-based interactive digital flipbook for fourth-grade whole-number multiplication material and to assess its feasibility limited to the aspect of validity. The development employed a Research and Development (R&D) approach using the systematic ADDIE model. During the design and development stages, the author created a storyboard and a flipbook prototype using Canva, which included sections such as a cover, basic material, story-based material, exercises, and explanations. The validity test was conducted through expert validation by lecturers from Universitas Jambi to evaluate the appropriateness of the content, the appearance/design and interactivity, and the language use, which then served as the basis for product revision. Validity data were collected using a 1–5 Likert-scale questionnaire and analyzed by calculating mean scores to determine the validity category; validity was assessed by a subject-matter expert, a media expert, and a language expert. The main result of the study was a story-based interactive digital flipbook product that had undergone expert review and was concluded to be valid as a learning medium for whole-number multiplication material. ABSTRAKPenelitian pengembangan ini dilatarbelakangi oleh hasil observasi di SD Negeri 74/III Dusun Baru yang menunjukkan pembelajaran matematika pada materi perkalian bilangan cacah belum memanfaatkan media berbasis teknologi secara optimal, sehingga siswa kurang antusias, kurang aktif, dan mengalami kesulitan memahami konsep karena pembelajaran masih didominasi penjelasan guru tanpa dukungan media interaktif yang membantu visualisasi konsep. Fokus penelitian adalah menghasilkan media flipbook digital interaktif berbasis cerita untuk materi perkalian bilangan cacah kelas IV serta menilai kelayakannya terbatas pada aspek validitas. Pengembangan dilakukan dengan pendekatan Research and Development (R&D) menggunakan model ADDIE yang sistematis. Pada tahap desain dan pengembangan, penulis menyusun storyboard dan prototype flipbook menggunakan Canva yang memuat bagian-bagian seperti cover, materi dasar, materi berbasis cerita, latihan, dan pembahasan. Uji validitas dilakukan melalui validasi ahli oleh dosen Universitas Jambi untuk menilai ketepatan isi materi, tampilan/desain serta interaktivitas, dan penggunaan bahasa, kemudian dijadikan dasar revisi produk. Data validasi dikumpulkan menggunakan angket skala Likert 1–5 dan dianalisis dengan menghitung rata-rata skor untuk menentukan kategori validitas; validitas dinilai oleh ahli materi, ahli media, dan ahli bahasa. Hasil utama penelitian berupa produk flipbook digital interaktif berbasis cerita yang telah melalui penilaian para ahli dan disimpulkan valid sebagai media pembelajaran pada materi perkalian bilangan cacah.